Influencia de la edad en el rendimiento de masa muscular en cuyes mejorados. Ayacucho, 2015 - Escobar Ramírez, Felipe (2016)
Influencia de la edad en el rendimiento de masa muscular en cuyes mejorados. Ayacucho, 2015